2011
DOI: 10.1016/j.jpubeco.2011.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The impact of research grant funding on scientific productivity

Abstract: In this paper, we estimate the impact of receiving an NIH grant on subsequent publications and citations. Our sample consists of all applications (unsuccessful as well as successful) to the NIH from 1980 to 2000 for standard research grants (R01s). Both OLS and IV estimates show that receipt of an NIH research grant (worth roughly $1.7 million) leads to only one additional publication over the next five years, which corresponds to a 7 percent increase. The limited impact of NIH grants is consistent with a mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
173
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 402 publications
(211 citation statements)
references
References 29 publications
16
173
1
3
Order By: Relevance
“…Our results are consistent with previous findings from two other NIH institutes, National Institute of General Medical Sciences 5 and NHLBI 3,4 , and from a unit at the National Science Foundation. 6 Furthermore, consistent with previous findings from NHLBI 4 and from NIH-wide analyses 14 , we found that productive applicants had better grant percentile rankings; consistent with previous NHLBI findings 4 , we found a moderate association between prior PI productivity and grant citation impact. We also found that basic science grants yielded greater citation impact than applied science grants, a finding supportive of NIMH's increasing focus on basic brain science.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are consistent with previous findings from two other NIH institutes, National Institute of General Medical Sciences 5 and NHLBI 3,4 , and from a unit at the National Science Foundation. 6 Furthermore, consistent with previous findings from NHLBI 4 and from NIH-wide analyses 14 , we found that productive applicants had better grant percentile rankings; consistent with previous NHLBI findings 4 , we found a moderate association between prior PI productivity and grant citation impact. We also found that basic science grants yielded greater citation impact than applied science grants, a finding supportive of NIMH's increasing focus on basic brain science.…”
Section: Discussionsupporting
confidence: 91%
“…For comparison, exactly the same dependence was also found in comparing the bibliometric data of applicants who participated in 17 FRIPRO competitions (Figure S1) [10]. In my opinion, an increase in the number of total publications ex-post reflects the general trend of the “maturation” of young scientists (in 5 of 6 studies [2], [6], [7], [10], [18] the average age of applicants varied from 32 to 46 years; in the Russian study – <35–40 years; in the Danish study [5] about 40% of applicants were aged up to 45 years), which is expressed in the progressive (until the age of 50) increase in the number of articles published every year [19]–[21]. Note that, judging by the data presented in Figure 4 and Figure S1, the “maturation” of frequently published young scientists (both awarded and rejected) happens faster.…”
Section: Discussionsupporting
confidence: 74%
“…Recent evidence on early career researchers shows that public funding for scientific career development impacts researchers most strongly in the early stage of their careers (Arora and Gambardella 2010). Postdoctoral grants, for example, were found to increase the number of articles researchers published in the 10 years following their award (Jacob and Lefgren 2011a). Another study by the same authors shows that postdoctoral grants increased the number of publications and citations during the five years following grant application by about 20% (Jacob and Lefgren 2011b).…”
Section: Literature Review: Funding and Research Performancementioning
confidence: 99%